Salt the water - Iloh, Candice (Dutton Books, an imprint of Penguin Random House LLC, 2023)
Raised in a free-spirited home by two loving parents who encourage Cerulean to be their full self, they've got big dreams of moving cross-country to live off the grid with their friends after graduation. When a fight with a teacher spirals out of control, Cerulean impulsively drops out to avoid the punishment they fear is coming. Why wait for graduation to leave an oppressive capitalist system and live their dreams? But their sheltered upbringing hasn't prepared them for the consequences of their choice--- especially when it is compounded by a family emergency that puts a parent out of work... and the money they'd been stacking with their friends is a resource that the family needs to stay afloat. -- adapted from jacket